Ocular morbidity in hearing impaired school children in Eastern Nepal - Dhungana, AP (Journal of Kathmandu Medical College, 2014)
Background: The association between deafness and ocular problems is well established; however the nature and prevalence of these problems are diverse across the globe. Objective: The aim of this study is to determine the nature and prevalence of ophthalmologic abnormalities in deaf students and offer treatment to those with remediable conditions. Method: Eighty seven deaf students aged between six and 25 years were examined in a school for the deaf. The study was cross-sectional and descriptive in nature. The research proforma was developed to collect the data. Data were analyzed using Microsoft Excel. Results: Twenty-three (26.43%) had some form of ophthalmologic abnormality. Some had anterior segment abnormalities such as corneal opacities (1.14%) and conjunctivitis (4.59%) while others had posterior segment abnormalities like optic atrophy (1.14%), and Ushers syndrome (1.14%). Refractive error was the most common (14.94%). Conclusion: Since these deaf students use their sight to compensate for the deafness, routine ophthalmologic examination should be carried out on them so that ophthalmologic abnormalities are detected early and treatment offered for remediable diseases DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10916 Journal of Kathmandu Medical College, Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 4-7